2000
DOI: 10.1001/archinte.160.13.1969
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Survival After Cardiopulmonary Resuscitation

Abstract: Background:The objective was to evaluate the effect of patient characteristics and other factors on cardiopulmonary resuscitation (CPR) survival, hospital discharge survival and function, and long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 31 publications
(25 reference statements)
2
43
2
7
Order By: Relevance
“…A few studies have examined long-term survival aft er hospital discharge among CPR recipients and found that 5% to 15% were alive at 6 months. 19,[29][30][31] A recent study linking data from the American Heart Association Get With the Guidelines (GWTG)-Resuscitation project with inpatient Medicare data reported that 58.5% of survivors who received CPR were alive at 1 year, 19 whereas median survival in all CPR recipients in the present study was lower at 11.1 months. Discrepancies in these results might be explained by diff erences in study populations because the present study included all Medicare benefi ciaries and the prior report included patients who received CPR at participating GWTG-Resuscitation hospitals.…”
Section: Figure 1 -Long-term Survival Among Cpr Recipients Who Survivmentioning
confidence: 55%
“…A few studies have examined long-term survival aft er hospital discharge among CPR recipients and found that 5% to 15% were alive at 6 months. 19,[29][30][31] A recent study linking data from the American Heart Association Get With the Guidelines (GWTG)-Resuscitation project with inpatient Medicare data reported that 58.5% of survivors who received CPR were alive at 1 year, 19 whereas median survival in all CPR recipients in the present study was lower at 11.1 months. Discrepancies in these results might be explained by diff erences in study populations because the present study included all Medicare benefi ciaries and the prior report included patients who received CPR at participating GWTG-Resuscitation hospitals.…”
Section: Figure 1 -Long-term Survival Among Cpr Recipients Who Survivmentioning
confidence: 55%
“…Long-term survival data following discharge from successful resuscitation demonstrate a poor prognosis. One-year mortality of 25% has been reported following cardiopulmonary resuscitation and discharge from hospital (24). The mortality rose to 46% at 2.5 years (25).…”
Section: Discussionmentioning
confidence: 99%
“…These policies served to establish procedures for writing DNR orders [2]. Research showed that about 5% of patients who required advanced cardiac life support (ACLS) outside the hospital and 15% of patients who required ACLS while in the hospital survive [3,4]. Elderly were living in nursing homes, had multiple medical problems, or who had advanced cancer been much less likely to survive [5].…”
Section: Introductionmentioning
confidence: 99%